2004
DOI: 10.1039/b403970j
|View full text |Cite
|
Sign up to set email alerts
|

Ionization-induced switch in aromatic molecule–nonpolar ligand recognition: Acidity of 1-naphthol+(1-Np+) rotamers probed by IR spectra of 1-Np+–Lncomplexes (L = Ar/N2, n ≤ 5)

Abstract: The interaction of the trans (t) and cis (c) rotamers of the 1-naphthol cation (1-C 10 H 8 O 1 ¼ 1-Np 1 ¼ 1-hydroxynaphthalene 1 ) with nonpolar ligands in the ground electronic state is characterized by IR photodissociation spectra of isolated 1-Np 1 -L n complexes (L ¼ Ar/N 2 ) and density functional calculations at the UB3LYP/6-311G(2df,2pd) level. Size-dependent frequency shifts of the O-H stretch vibration (Dn 1 ) and photofragmentation branching ratios provide information about the stepwise microsolvatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
67
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 85 publications
6
67
1
Order By: Relevance
“…As TRA + is expected to form weak H-bonds with nonpolar N 2 molecules, their characteristic features become accessible by direct comparison with the strong conventional H-bond observed in TRA + -H 2 O. The current TRA + -(N 2 ) n study extends our previous characterization of A + -(N 2 ) n clusters with more simple aromatic chromophores (A + ), 32 such as benzene, 33,34 phenols and naphthols, [35][36][37][38][39] anilines, [40][41][42] imidazole, 43 cyclopropenyl, 44,45 and indole (In). 46 These studies revealed that the microsolvation process of acidic aromatic ions in molecular nitrogen is dominated by the competition between two principal binding motifs, namely H-bonding to the acidic functional OH and NH groups and p-stacking to the aromatic ring.…”
Section: Introductionsupporting
confidence: 58%
“…As TRA + is expected to form weak H-bonds with nonpolar N 2 molecules, their characteristic features become accessible by direct comparison with the strong conventional H-bond observed in TRA + -H 2 O. The current TRA + -(N 2 ) n study extends our previous characterization of A + -(N 2 ) n clusters with more simple aromatic chromophores (A + ), 32 such as benzene, 33,34 phenols and naphthols, [35][36][37][38][39] anilines, [40][41][42] imidazole, 43 cyclopropenyl, 44,45 and indole (In). 46 These studies revealed that the microsolvation process of acidic aromatic ions in molecular nitrogen is dominated by the competition between two principal binding motifs, namely H-bonding to the acidic functional OH and NH groups and p-stacking to the aromatic ring.…”
Section: Introductionsupporting
confidence: 58%
“…44 As the binding energies and potential barriers for Ar clusters interacting with PhOH and benzene are of similar magnitude, the melting temperatures for both cluster systems are expected to be similar, too. Interestingly, the simulations reveal that at temperatures above melting and below boiling (evaporation) the less stable (20) isomer of benzene-Ar 2 is more abundant than the more stable (11) isomer due to entropy. 44 Spectroscopic 12,13,15 and theoretical studies 12,14,35,45 show that in the cationic D 0 state the H-bonded (H00) structure is the global minimum on the PhOH + -Ar potential and more stable than the p-bonded (10) local minimum.…”
mentioning
confidence: 99%
“…[3][4][5][7][8][9][10][11] Neutral PhOH-Rg dimers prefer p-bonding because dispersion dominates the attraction, whereas PhOH + -Rg cations prefer H-bonding because the additional charge-induced polarisation forces provide substantial further stabilisation. 12,13 This charge-induced p -H switch is a general phenomenon for acidic aromatic molecules interacting with nonpolar ligands, 4 and has been established for a variety of aromatic molecules with acidic OH or NH functional groups, including phenol, [12][13][14][15][16][17][18] resorcinol, 19 naphthol, 20 aniline, [21][22][23] indole, 24 and imidazole. 25 The present work characterizes the structures, binding energies, and vibrational and electronic spectra of various isomers of neutral and ionic PhOH (+) -Ar n clusters with n r 4 by quantum chemical calculations in three different electronic states, namely the neutral ground and first excited singlet states (S 0 , S 1 ) and the cation ground state (D 0 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the corresponding A + -L dimer cations usually prefer H-bonds with the acidic functional group(s) due to additional charge-induced interactions arising from the excess charge. 9,13 This ionization-induced p -H switch in the preferred A (+) -L binding motif has recently been established via the combination of IR spectroscopy and quantum chemical calculations for a variety of acidic aromatic molecules interacting with rare gas (Rg) atoms, CH 4 , and N 2 , 9 including (substituted) phenols, [13][14][15][16][17][18][19][20][21][22] naphthol, 23 aniline, [24][25][26] aminobenzonitrile, 27,28 imidazole, 29,30 indole, 31 and tryptamine. 32 In some of these clusters, this ionization-induced p -H switch triggers an intermolecular isomerization reaction upon photoionization, which occurs on the picosecond timescale [33][34][35] and is usually inferred from IR spectra recorded before and after ionization using nanosecond laser systems.…”
Section: Introductionmentioning
confidence: 99%